Cloning and Overexpression of Strictosidine β-D-Glucosidase Gene Short Sequence from Catharanthus roseus in Escherichia coli - Ahmed Saeed Arafa; Amany Elsayed Ragab; Abdel-Rahim Sayed Ibrahim; Wael Saad Abdel-Mageed; Mahmoud Emam Nasr (Tabriz University of Medical Sciences, 2019)
Purpose: Strictosidine-β-D-glucosidase (SGD) is considered as a key enzyme in the production of bisindole alkaloids in Catharanthus roseus. The present study illustrated the production of a short sequence of this enzyme in Escherichia coli without codon optimization. Methods: Strictosidine-β-D-glucosidase (sgd) gene short sequence (1434 bp), which lacks the conserved sequence KGFFVWS and the localization peptide sequence at the C-terminal, was amplified from cDNA of C. roseus leaves, cloned and expressed in Escherichia coli. The activity of the produced protein in cell free lysate was tested using total alkaloid extract of C. roseus leaves. Results: HPLC and LC-MS analysis of the assay mixture revealed the disappearance of the strictosidine peak. Conclusion: SGD short sequence can be produced in Escherichia coli in active form without codon optimization.